Violence and the genesis of the anatomical image - San Juan, Rose Marie (Penn State University Press, 2022)
Nothing excited early modern anatomists more than touching a beating heart. In his 1543 treatise, Andreas Vesalius boasts that he was able to feel life itself through the membranes of a heart belonging to a man who had just been executed, a comment that appears near the woodcut of a person being dissected while still hanging from the gallows. In this highly original book, Rose Marie San Juan confronts the question of violence in the making of the early modern anatomical image.Engaging the ways in which power operated in early modern anatomical images in Europe and, to a lesser extent, its colonies, San Juan examines literal violence upon bodies in a range of civic, religious, pedagogical, and “exploratory” contexts. She then works through the question of how bodies were thought to be constituted—systemic or piecemeal, singular or collective—and how gender determines this question of constitution. In confronting the issue of violence in the making of the anatomical image, San Juan explores not only how violence transformed the body into a powerful and troubling double but also how this kind of body permeated attempts to produce knowledge about the world at large.Provocative and challenging, this book will be of significant interest to scholars across fields in early modern studies, including art history and visual culture, science, and medicine